FORMATION OF SMALL-SCALE STRUCTURES IN THEINTERSTELLAR MEDIUM - Matvienko, E. E.; Vasiliev, E. O.; Shchekinov, Yu. A. (Одеські астрономічні публікації, 2008)
We consider formation of small scale structures in the process of interstellar cloud destruction by shock waves. We calculate statistical properties of HI column densities, optical depth and brightness temperature in 21 cm line. We discuss possible relation of the small-scale structures found in numerical models to the so called "low-N(HI)" clouds observed recently in the interstellar medium.